Financial impact of needle stick injury on a tertiary care teaching hospital - Snehal Dhayagude; Anuradha Tolpadi; Abhijeet Mane; Meera Modak (Elsevier, 2024)
Background: Accidental needle stick injuries (NSIs) are an occupational hazard for healthcare workers (HCWs). Despite the implementation of preventive measures, NSIs still continue to occur in health care settings. The cost incurred by an institute for the management of occupational exposure to blood borne pathogen is a significant economic burden.This retrospective study was aimed to estimate the prevalence, factors associated with NSIs and cost burden on hospital due to NSIs. Material and methods: Retrospective data of all reported NSIs among HCWs between January 2019 and December 2021 in a tertiary care hospital was collected and analyzed. CDC definition was used to calculate direct & indirect cost. Results: & Discussion- A total 205 NSIs were reported between January 2019 and December 2021. Nurses were the most affected category of HCWs. The maximum number of NSI cases (18.54 %) occurred during handling of biomedical waste. Both the source and the affected HCWs were tested and it was found that the source was seropositive in 30(14.63 %), seronegative in 128 (62.44 %) cases and in 47(22.93 %) cases there was an unknown source resulting in NSI. A total of 13, 21,206 INR, which included both direct and indirect cost, spent by hospital in the management of NSI's, over a period of 3yrs. Conclusion: Surveillance and analysis of NSI is very crucial for the planning of both preventive measures and training modules. Managing NSI generates significant cost. Hepatitis B vaccination for all healthcare workers plays major role in reducing cost of managing NSIs.